Measuring financial performance in infrastructure : an application to Europe and Central Asia - Ebinger, Jane O.; World Bank. (Washington, D.C. : World Bank, Europe and Central Asia Region, Infrastructure and Energy Services Dept., 2006)
"The authors examine how well several institutional and firm-level factors and their interactions explain firms' perceptions of property rights protection. Their sample includes private and public firms that vary in size from very small to large in 62 countries. Together, the institutional theories they investigate account for approximately 70 percent of the country-level variation, indicating that the literature is addressing first-order factors. Firm-level characteristics such as legal organization and ownership structure are comparable to institutional factors in explaining variation in property rights protection. A country's legal origin and formalism index predict property rights variation better than its openness to international trade, its religion, its ethnic diversity, natural endowments or its political system. However, these results are driven by the inclusion of former socialist economies in the sample. When the authors exclude the former socialist economies, legal origin explains considerably less than openness to trade and endowments. Examining a broader set of variables for robustness, they again find that when they exclude former socialist countries, legal origin explains comparatively little of the variation in perceptions of judicial efficiency, corruption, taxes and regulation, street crime, and financing. "--World Bank web site.
Includes bibliographical references.
Also available in print.
System requirements: Adobe Acrobat Reader.
Mode of access: World Wide Web.
Zahid
Keywords: Public utilities -- Europe; Public utilities -- Asia, Central